Probing medium response via strangeness enhancement around quenched jets - Ao Luo; Shanshan Cao; Guang-You Qin (Physics Letters B)
Jet-induced medium excitation is a crucial part of jet interactions with the quark-gluon plasma (QGP) in relativistic heavy-ion collisions, and has recently been confirmed by experiment for the first time. Based on the AMPT model simulation, we propose the strangeness enhancement around quenched jets as a novel signature of jet-induced medium excitation. By applying the jet-particle correlation techniques, we calculate jet-induced particle yields around the jets and find a significant enhancement of the strange-to-non-strange-hadron ratio and the double-to-single-strange-hadron ratio correlated with jets in relativistic nucleus-nucleus collisions relative to proton-proton collisions. This enhancement increases with both the strength of jet-QGP interactions and the radial distance from jet axis. These observations align with the features of jet-induced medium excitation and parton coalescence in hadron formation, and await experimental validation in the future measurements.